2006
DOI: 10.1021/jp051692m
|View full text |Cite
|
Sign up to set email alerts
|

How Does Ammonium Dynamically Interact with Benzene in Aqueous Media? A First Principle Study Using the Car−Parrinello Molecular Dynamics Method

Abstract: The Car-Parrinello molecular dynamics (CPMD) method was used to study the dynamic characteristics of the cation-pi interaction between ammonium and benzene in gaseous and aqueous media. The results obtained from the CPMD calculation on the cation-pi complex in the gaseous state were very similar to those calculated from the Gaussian98 program with DFT and MP2 algorithms, demonstrating that CPMD is a valid approach for studying this system. Unlike the interaction in the gaseous state, our 12-ps CPMD simulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 60 publications
3
38
1
Order By: Relevance
“…However, the ammonium interacts with benzene in water mostly through three of its hydrogen atoms, which is different from the interaction in the gaseous state via two hydrogen atoms. The interaction between ammonium and benzene is invaded by water molecules, resulting in a calculated binding free energy of −5.75 kcal·mol −1 , which is similar to the strength of a conventional hydrogen bonding in aqueous solution [45] . …”
Section: Theoretical Studies On Cation-π Interactionsmentioning
confidence: 61%
See 2 more Smart Citations
“…However, the ammonium interacts with benzene in water mostly through three of its hydrogen atoms, which is different from the interaction in the gaseous state via two hydrogen atoms. The interaction between ammonium and benzene is invaded by water molecules, resulting in a calculated binding free energy of −5.75 kcal·mol −1 , which is similar to the strength of a conventional hydrogen bonding in aqueous solution [45] . …”
Section: Theoretical Studies On Cation-π Interactionsmentioning
confidence: 61%
“…Different cation-π systems possess different proportions of binding components. Since 1997, Zhu and Jiang et al [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] have performed systematic investigations on cation-π interactions by quantum chemical methods. The investigated cations included alkali metal, alkaline-earth metal, NH 4 + , CH 3 NH 3 + , and tetramethylammonium (TMA); the aromatic systems included benzene, substituted benzene, 5-membered and 6-membered aromatic heterocyclic rings, 8-membered aromatic rings, all kinds of aromatic residues and nucleobases.…”
Section: Theoretical Studies On Cation-π Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) sampling conformations of small flexible molecules and peptides [18][19][20]; (2) environmental effects on covalent bond formation/breaking (usually in combination with ab initio MD) [21][22][23][24][25][26][27]; (3) solvation and non-covalent binding of small molecules in solvent [28][29][30][31][32]; (4) protein dimerization [33,34].…”
Section: Blue-moon Samplingmentioning
confidence: 99%
“…Early in 1986, Burley and Petsko examined 33 high resolution (2 Å or higher), refined protein crystal structures and demonstrated that positively charged or δ (+) amino groups, like lysine and arginine, tend to be located within 6 Å of the ring centroids of aromatic amino acids, where they form van der Waals' contacts with the δ (-) π-electrons [31]. Although solvent water molecules can affect the cation-π interaction, its strength was still considerable with the H-bonds in aqueous solution [32]. Considering the combined effect of the compounds and the residues in the pocket, compound 2-2 showed better activity than compound 2 , as manifested in the IC 50 values.…”
Section: Resultsmentioning
confidence: 99%